Development of Knowledge Management System of Teachers’ Competency - Annisa Saraswati; Irman Hermadi; Sony Hartono Wijaya (Jurnal Pendidikan Teknologi dan Kejuruan, 2019)
Teachers had a strategic role in helping achieving an educational purpose. Every teacher should have specific competencies. Sustainable quality improvement of teachers needed to get support and attention from various stakeholders including leaders at schools and government.  Therefore, a medium was required to facilitate the process of various knowledge of teacher competency which had been documented and unlimited to time and location. One of the solutions was developing a knowledge management system. The research method was adopted from Knowledge Management System Life Cycle (KMSLC) method. Results of this research was a web-based knowledge management system with features supporting the process of capturing, developing, distributing, and utilizing knowledge. Development of the knowledge management system could facilitate teachers to gain knowledge related to teachers’ competencies easily.